Foundations of intelligent systems : 24th International Symposium, ISMIS 2018, Limassol, Cyprus, October 29-31, 2018, Proceedings /: 24th International Symposium, ISMIS 2018, Limassol, Cyprus, October 29-31, 2018, Proceedings. (2018) - Unknown
No abstract available